45 Quality Improvement Project on Delirium Care in Older Patients at Mid Yorkshire Hospitals NHS Trust (MYHT). (16th March 2021) - Mon, H; Holt, R
Abstract: Background: To improve delirium care in older patients admitted to a large district general NHS Trust in the UK, a quality improvement project was conducted. Introduction: The national NICE guidelines (CG103) and recent SIGN guidelines recommend delirium is diagnosed by a clinical assessment based on DSM criteria (e.g. CAM or 4AT) and managed by identifying and treating the causes alongside multicomponent interventions. The results of MYHT's 2018 delirium audit showed the use of CAM or 4AT was 32.5% and delirium care plan was 20%. A quality improvement project was developed and implemented for 6 weeks on a frailty admission unit. Method: The quality improvement project introduced a delirium care checklist sticker for medical notes in cases of suspected delirium, brief education sessions for ward doctors regarding delirium care and use of the sticker and reminder emails, all implemented by the elderly medicine registrar. The target measures were completion of stickers, 4AT and delirium care plan. Data was collected by the registrar once a week for 6 weeks and entered into a run chart. Feedback was collected from staff on barriers to use. Results: 31 patients with suspected delirium has their notes reviewed. The sticker use gradually reduced from 57% of cases in week 1, to 0% in week 6. The 4ATwas completed in 57%, 50% and 100% of cases in the first 3 weeks, but dropped to 40%, 4.2% and 1.3% in the last 3 weeks. A delirium care plan was initiated in 42% and 37% of cases in the first two weeks but ended at 0% by week 6. Barriers included a lack of education sessions from week 2 onwards due to registrar on call shifts. Also junior doctor changeover in week 3. Feedback indicated barriers were time taken to complete, and confusion over ownership of completing 4AT and care plan between medical and nursing teams. Conclusion: Although a delirium care checklist sticker and brief education sessions can improve delirium care, sustained improvement requires ongoing education and addressing barriers to completion. References: 1. National Institute for Health and Care Excellence (2019) Delirium: prevention, diagnosis and management (NICE Guideline CG103). Available at: https://www.nice.org.uk/guidance/cg103 Accessed 21/09/2019]. 2. Scottish Intercollegiate Guidelines Network (2019) risk reduction and management of delirium (SIGN Guideline 157). Available at https://www.sign.ac.uk/assets/sign157.pdf . Accessed 21/09/2019.